2000
DOI: 10.1515/mamm.2000.64.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Sugar discrimination and gustatory thresholds in captive-born frugivorous Old World Bats

Abstract: In general, preference for different sugars in nectarivores and frugivores is related to the composition of their food. We determined individual preferences in Cynopterus brachyotis and Pteropus rodriccnsis, and group preferences in one group of P. rodricensis and two mixed groups of P. rodricensis, P. pumilus, P. vampyrus, and P. hypomelanus. Most bats were born in captivity and received a diet with a composition of sugars of sucrose = glucose > fructose during 1 to 6 years before the experiment. We tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2003
2003
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…2 ). Similar behavioral preference was also recorded in two other Old World frugivorous bats ( 38 ). Cell-based assays consistently demonstrated that the sweet taste receptors of two Old World frugivorous bats ( R. aegyptiacus and P. vampyrus ) showed clear dose-dependent responses to sucrose and fructose, although not to glucose ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…2 ). Similar behavioral preference was also recorded in two other Old World frugivorous bats ( 38 ). Cell-based assays consistently demonstrated that the sweet taste receptors of two Old World frugivorous bats ( R. aegyptiacus and P. vampyrus ) showed clear dose-dependent responses to sucrose and fructose, although not to glucose ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The Egyptian fruit bats' preference for sucrose over fructose, and for fructose over glucose, is similar to that of other Old World fruit bats, and this pattern has been explained by the lower threshold for tasting sucrose than fructose or glucose in these bats (Herrera et al, 2000). The pattern of sugar preferences shown by female and male bats was very similar; however, females did not appear to find differences between fructose and glucose in ethanol-free mixtures, whereas males did.…”
Section: Discussionsupporting
confidence: 53%
“…While the role of amino acids for food selection in pteropodid and phyllostomid bats is unknown, bats can use olfactory cues to find food sources (Rieger & Jakob ; Laska ; Thies, Kalko & Schnitzler ; von Helversen, Winkler & Bestmann ). Furthermore, they respond differently to the taste of the three most common sugar types found in nectar, indicating the existence of an ability to discriminate between subtle variation in nectar flavour (Herrera, Leblanc & Nassar ; Ayala‐Berdon et al . ).…”
Section: Introductionmentioning
confidence: 99%